2011
DOI: 10.1007/s11325-011-0515-z
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic characteristics of daytime sleepiness in obstructive sleep apnea syndrome

Abstract: The results suggest that EDS in OSAS patients are characterized by the following aspects of nocturnal sleep: (1) severe sleep apnea/hypopnea and hypoxemia, (2) fragmented sleep, (3) low quality of sleep, and (4) high pressure of sleep drive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 27 publications
4
41
1
3
Order By: Relevance
“…BMI was also one of the three major determinants of the ESS score [6]. Our study showed that BMI was also significantly greater in the EDS patients than in the no-EDS patients, suggesting that obesity may have an effect on the severity of OSA in accordance with previous studies [5,6,10,12,13], contrary to other studies [11].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…BMI was also one of the three major determinants of the ESS score [6]. Our study showed that BMI was also significantly greater in the EDS patients than in the no-EDS patients, suggesting that obesity may have an effect on the severity of OSA in accordance with previous studies [5,6,10,12,13], contrary to other studies [11].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, nocturnal oxygenation indices were significantly worse [higher ODI, lower minimum SpO 2 and longer time (SpO 2 \ 90%)] in the EDS patients compared to the patients without EDS. Thus, our findings, like others [2,6,10,11], suggest that nocturnal hypoxemia may have a significant role in the pathogenesis of EDS in OSA patients with considerable consistency. Although the exact biological mechanisms are unknown, it was postulated that increased hypoxemia causes severe neural damage of wake-promoting structures, leading to EDS [15].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations